Swimming techniques in action - Lynn, Alan; Cryer, Nigel; Condie, John; Crowood Films ([ Ramswood, England ] : Crowood Films, 2007)
Alan explains stroke drills to practise, gives tips to improve performance and highlights good behaviour for training and competition. He also illustrates the crucial racing skills of starts and turns for each stroke and for the individual medley
Coach: Alan Lynn
DVD format
Keywords: Swimming; Swimming -- Coaching